Anxiety among healthcare workers during the COVID-19 pandemic: a longitudinal study - Bosma, Esmee; Feenstra, Verena; van Oostrom, Sandra H.; , Lifelines Corona Research Initiative; Marike Boezen, H.; Mierau, Jochen O.; Lude Franke, H.; Dekens, Jackie; Deelen, Patrick; Lanting, Pauline; Vonk, Judith M.; Nolte, Ilja; et al. (Frontiers in Public Health, 2023)
Background: During the COVID-19 pandemic, many healthcare workers faced extreme working conditions and were at higher risk of infection with the coronavirus. These circumstances may have led to mental health problems, such as anxiety, among healthcare workers. Most studies that examined anxiety among healthcare workers during the COVID-19 pandemic were cross-sectional and focused on the first months of the pandemic only. Therefore, this study aimed to investigate the longitudinal association between working in healthcare and anxiety during a long-term period (i.e. 18 months) of the COVID-19 pandemic. Methods: Data were used from online questionnaires of the Lifelines COVID-19 prospective cohort with 22 included time-points (March 2020-November 2021). In total, 2,750 healthcare workers and 9,335 non-healthcare workers were included. Anxiety was assessed with questions from the Mini-International Neuropsychiatric Interview, and an anxiety sum score (0-7) was calculated. Negative binomial generalized estimating equations (GEE), adjusted for demographic, work and health covariates, were used to examine the association between working in healthcare and anxiety. Results: Anxiety sum scores over time during the COVID-19 pandemic were similar for healthcare workers and non-healthcare workers. No differences between the anxiety sum scores of healthcare workers and non-healthcare workers were found (incidence rate ratio (IRR) = 0.97, 95% CI = 0.91-1.04). Conclusion: This study did not find differences between healthcare workers and non-healthcare in perceived anxiety during the COVID-19 pandemic.